An Interpretation of the Urban Digital Economy Effecting Manufacturing Innovation Efficiency - Shengsheng Li; Yuanyuan Wang; Xing Xu (SAGE Open)
This study analyzes the effect of urban digital economy (UDE) development on manufacturing innovation efficiency from the perspectives of urban industrial agglomeration and government subsidies, using mixed panel data of Chinese cities and A-share manufacturing listed companies from 2011 to 2019. This study reveals the following findings: (1) There is a threshold effect of government subsidies and industrial agglomeration on the impact of UDE on the innovation efficiency of listed manufacturing industries. Quantitatively, the study identifies two thresholds for industrial agglomeration (−3.7468 and −1.5172) and two thresholds for government subsidies (16.6139 and 18.2936). (2) The impact of UDE on the innovation efficiency of the manufacturing industry is significantly enhanced with the increase in the level of urban industrial agglomeration. (3) The threshold effect of government subsidies is evident when the impact becomes more pronounced as government subsidies increase. Finally, we find regional and firm size heterogeneity in the effects from government subsidies and industrial agglomeration. This study broadens the scope of the study by considering government subsidies at the firm level and industrial agglomeration at the city level. There is a nonlinearity in the effect of UDE on manufacturing innovation efficiency. This finding enriches the theoretical framework of the relationship between UDE and firms’ innovation efficiency. Meanwhile, the findings provide clear guidance for policymakers: in the process of promoting the integration of the digital economy and the manufacturing industry, attention should be paid to optimizing the industrial agglomeration environment and the rational allocation of government subsidy resources.